2008
DOI: 10.1051/alr:2008028
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale exploitation of a major tuna concentration in the Indian Ocean

Abstract: The paper analyzes the daily catch, fishing effort and fish size data of the purse seine fleet fishing in the western Indian Ocean in February 2005, when a major concentration of tuna occurred and was heavily exploited by this surface fishery. This tuna concentration event occurred over a period of just 12 days, in an area of about 3500 square nautical miles located to the west of the Seychelles. This small stratum produced a total catch of 22 000 t, corresponding to 6.5% of the total fishing mortality of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 9 publications
0
28
0
1
Order By: Relevance
“…This attracts nekton, with a net effect of aggregation of apex predators to forage on the lower trophic level organisms around the eddy edge (Ramos et al. , 1996; Fonteneau et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This attracts nekton, with a net effect of aggregation of apex predators to forage on the lower trophic level organisms around the eddy edge (Ramos et al. , 1996; Fonteneau et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…(2008) determined that relatively low concentrations of chlorophyll a were optimum for longline capture of YFT in the Northern Indian Ocean. Conversely, anomalously large purse seine catches in the equatorial Western Indian Ocean were linked to a high concentration phytoplankton bloom associated with a large anticyclonic eddy (Fonteneau et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the rest of variables, Fonteneau et al () found interesting relationships between chlrophyll‐a peak levels 18 days prior and free‐swimming tuna abundance in the Indian Ocean. However, and in accordance with the work of Lopez, Alvarez‐Berastegui, et al, , Lopez, Moreno, et al, , these relationships have not been found yet in the Atlantic Ocean for tuna and nontuna species.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll plays a key role in marine ecosystems as it is the source of the energy circulating through the trophic levels, and therefore, it can be seen as a proxy of prey enrichment (Marsac, ). In this study, chlorophyll taken 18 days before was selected as Fonteneau, Lucas, Tewkai, Delgado, and Demarcq () found interesting relationships between circumstantial Chl‐a levels 18 days before and free‐swimming tuna abundance in the Indian Ocean. Moreover, this variable has been also studied for the same reasons in the Atlantic Ocean to study relationships between environment characteristics and tuna distributions in DFAD sets (López, ).…”
Section: Methodsmentioning
confidence: 99%